Modelling the effectiveness of nutritional interventions in children under five years in Mangochi, Malawi - Mwingirwa, Karimi Fridah (My University, 2018)
Background Malnutrition rates in children under five years remain considerably high, despite many singular interventions to prevent and control undernutrition that have not been successful. Part of the reason for this is, the design of these interventions does not take into consideration whether a singular intervention in a multifactorial caused problem could be effective and that there is need to simulate beforehand what will work before it is implemented. There have been few studies investigating the effectiveness of these interventions in the reduction of the incidence and prevalence of stunting, wasting and underweight in children. The main aim of this study was to develop a simulated mathematical model that informs the effectiveness of nutritional and education interventions for stunting, wasting and underweight in children under five years of age. Methods The methodology was two-pronged; Firstly, demographic characteristics and prevalence of stunting, underweight and wasting, including risk factors were obtained from secondary analysis of an intervention study conducted in Mangochi, Malawi whereby, 840 children were randomised to receive; micronutrient-fortified lipid-based nutrient supplements(LNSs) with soy protein base, micronutrient-fortified LNSs with milk protein base and micronutrient-fortified corn–soy blend for 12 months. Demographic characteristics were compared using Fisher‟s exact test and Pearson‟s Chi square test and risk factors assessed using univariate and multivariable logistic regression models. This analysis provided baseline factors for the simulation analysis. Secondly, malnutrition rates, recovery rates and supplementary feeding parameters obtained in the first analysis and health education parameters obtained from the literature were used to simulate a deterministic mathematical model. The interventions considered were supplementary feeding and health education applied singly and when combined. Supplementary feeding coverage was defined by inclusion and by the participant being in the programme for a minimum duration of 12 weeks; health education coverage was defined by intensity and by the participant being in the programme for a minimum duration of 12 weeks; whereas the combined intervention was defined by both inclusion, intensity and by the participant being in the programme for a minimum duration of 12 weeks. Sensitivity analysis was done by varying the model parameters through simulations and associated outputs assessed. Results The prevalence of stunting, wasting, underweight and overweight was approximately 37%, 2%, 14% and 7% respectively. Risk factors changed by the type of malnutrition. Maternal education, maternal Mid Upper Arm Circumference (MUAC), mosquito net ownership and sex of the child were associated with stunting. Type of toilet facility, the number of children under five and maternal MUAC were associated with underweight. Our results showed that; female children and children from households with mosquito nets were less likely to be stunted or underweight. Health education intervention had a significantly larger reduction in incidence and the prevalence of stunting, wasting and underweight compared to supplementary feeding when applied singly. The highest reduction in malnutrition in children under five years was observed after combining supplementary feeding and health education. Malnutrition decreased with an increase in the coverage of the intervention. Discussion Health education has a bigger effect on prevention and control of all forms of malnutrition compared to supplementary feeding as a single intervention. Households with their available resources can have improved nutrition statuses without any supplementary feeding, provided that caregivers are educated on improving feeding behaviours, effective child care practices and proper hygiene. The addition of supplementary feeding to health education (combined intervention) improves the effect size of a single intervention in the reduction of the prevalence and incidence of malnutrition. Therefore, nutritional education interventions should be implemented in combination with affordable supplementary feeding, particularly in middle and low-income countries that are food insecure.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, South Africa, in partial fulfilment of requirements for Masters of Science in Epidemiology in the field of Biostatistics degree. January 2018.
Keywords: Nutritional Intervention; Child Nutrition Disorders